2022
DOI: 10.1093/oncolo/oyab008
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study Evaluating Dose De-escalation of Sorafenib with Metformin and Atorvastatin in Hepatocellular Carcinoma (SMASH)

Abstract: Background This phase I dose de-escalation study aimed to assess the tolerability, safety, pharmacokinetics (PK), and efficacy of sequentially decreasing doses of sorafenib in combination (SAM) with atorvastatin (A, 10 mg) and metformin (M, 500 mg BD) in patients with advanced hepatocellular carcinoma (HCC). Methods Patients were enrolled in 1 of 4 sequential cohorts (10 patients each) of sorafenib doses (800 mg, 600 mg. 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our study evaluated a feasible dose de-escalation strategy involving two FDA-approved drugs, sorafenib and metformin, which can potentially reduce the side effects associated with these drugs as well as provide increased efficacy. Our results are supported by a recent study showing that reduced doses of sorafenib along with standard doses of atorvastatin and metformin led to reduced sorafenib-related side effects in advanced HCC [ 60 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our study evaluated a feasible dose de-escalation strategy involving two FDA-approved drugs, sorafenib and metformin, which can potentially reduce the side effects associated with these drugs as well as provide increased efficacy. Our results are supported by a recent study showing that reduced doses of sorafenib along with standard doses of atorvastatin and metformin led to reduced sorafenib-related side effects in advanced HCC [ 60 ].…”
Section: Discussionsupporting
confidence: 86%
“…Randomized efficacy trials evaluating the clinical benefit of metformin were also carried out in patients with bladder 105 , cervical 106 , esophageal 107 , liver 108 , ovary 109 , 110 , pancreas 111 , 112 and prostate cancer 113 , 114 , 115 . Although some human studies have shown the protective effect of metformin on cancer development, many prospective studies failed to show the improvement in primary endpoints, such as disease‐free survival (DFS) and overall survival, in cancer‐bearing patients treated with metformin plus standard cancer therapy.…”
Section: Metformin and Cancermentioning
confidence: 99%
“…Contrary to the possible risk of SGLT2is for cancer incidence, many preclinical studies have shown the protective effects of SGLT2 inhibition in cancer progression. Several basic and clinical investigations have elucidated that SGLT2is could mitigate the development of nonalcoholic steatohepatitis 108 , which is one of the important risk factors of liver cancer initiation or promotion. In this line, animal studies showed that a SGLT2i canagliflozin attenuates the development of hepatocellular carcinoma through the suppression of hepatic steatosis, inflammation, fibrosis and pro‐angiogenic activity 174 , 175 , 176 .…”
Section: Sodium–glucose Cotransporter 2 Inhibitors and Cancermentioning
confidence: 99%
“… 50 In a phase I dose de-escalation study aimed to assess the safety and efficacy of sequentially decreasing doses of sorafenib in combination with atorvastatin (10 mg once daily) and metformin (500 mg twice daily), there was a marked reduction in sorafenib-related side effects. 51 Both these drugs show an inhibitory effect against chronic hepatitis and liver cirrhosis and also resensitize HCC cells to the action of sorafenib.…”
Section: Treatment Modalities For Hccmentioning
confidence: 99%